Chinese and Thai consumers’ willingness to pay for quality rice attributes: a discrete choice experiment method - Achara Boonkong; Baichen Jiang; Fallah Samuel Kassoh; Fallah Samuel Kassoh; Tanapon Srisukwatanachai (Frontiers in Sustainable Food Systems, 2023)
Food safety scandals have heightened the general public concern about food quality, safety, and environmental friendliness in food markets globally. Several studies have ascertained that consumers are willing to pay a premium price for food products with quality and safety information labels. However, most of these studies are country-specific, while few studies have investigated consumer preferences in a comparative context. In this study, we employed the Discrete Choice Experiment (DCE) to examine 1,900 Chinese and 2,986 Thai consumers’ willingness-to-pay (WTP) for brand, traceability, and green and organic certification labels on rice. A mixed logit model (MXL) was used to compute consumers’ WTP. The results demonstrate that consumers from both countries preferred green and organic certified labels. However, Chinese consumers’ preference for green and organic certified rice outweighs that of Thai consumers. For brand labels and green and organic certifications, Thai consumers are willing to pay more than the Chinese due to awareness and trust. However, Chinese consumers are willing to pay more for information with traceability labels than Thai consumers because of the increase in household income and health consciousness. The MXL also shows that trust, income, and age are factors associated with consumers’ preferences for certified rice in both countries. To boost consumers’ preferences for certified rice, relevant stakeholders need to implement the use of brand labels, traceability, and certification labels in the rice value chain.